2017
DOI: 10.1002/ejoc.201701381
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Anionic Alkoxide–Allene and Amide–Allene Cyclizations

Abstract: Computational studies have been performed on potassium alkoxide‐allenes, as well as potassium and lithium amido‐allenes to probe the mechanism of their cyclizations to dihydrofurans and to 2,5‐dihydropyrroles. A long‐standing proposal envisaged electron transfer from dimsyl anions (formed by deprotonation of the solvent DMSO) but this pathway shows an exceptionally high kinetic barrier, while direct 5‐endo‐trig cyclization of the alkoxides and amides is much more easily achievable. The energy profiles for 4‐ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Recent DFT calculations of cyclizations of allenylamines without the 3‐alkyl group revealed that the anionic pathway is energetically feasible. For N ‐tosyl derivatives an energy barrier in the range of 28 kcal/mol was calculated and the cyclization is endergonic (Δ G ≈ 13 kcal) reflecting the relatively high energy of the resulting 2,5‐dihydropyrrole anion . These calculations also indicate that a pathway involving an electron transfer process with radicals as intermediates is very unlikely.…”
Section: Resultsmentioning
confidence: 95%
“…Recent DFT calculations of cyclizations of allenylamines without the 3‐alkyl group revealed that the anionic pathway is energetically feasible. For N ‐tosyl derivatives an energy barrier in the range of 28 kcal/mol was calculated and the cyclization is endergonic (Δ G ≈ 13 kcal) reflecting the relatively high energy of the resulting 2,5‐dihydropyrrole anion . These calculations also indicate that a pathway involving an electron transfer process with radicals as intermediates is very unlikely.…”
Section: Resultsmentioning
confidence: 95%